Berberine: Botanical Occurrence, Traditional Uses, Extraction Methods, and Relevance in Cardiovascular, Metabolic, Hepatic, and Renal Disorders - Echeverria-Morgado, J (Frontiers Media S.A., 2018)
Berberine-containing plants have been traditionally used in different parts of the world for the treatment of inflammatory disorders, skin diseases, wound healing, reducing fevers, affections of eyes, treatment of tumors, digestive and respiratory diseases, and microbial pathologies. The physico-chemical properties of berberine contribute to the high diversity of extraction and detection methods. Considering its particularities this review describes various methods mentioned in the literature so far with reference to the most important factors influencing berberine extraction. Further, the common separation and detection methods like thin layer chromatography, high performance liquid chromatography, and mass spectrometry are discussed in order to give a complex overview of the existing methods. Additionally, many clinical and experimental studies suggest that berberine has several pharmacological properties, such as immunomodulatory, antioxidative, cardioprotective, hepatoprotective, and renoprotective effects. This review summarizes the main information about botanical occurrence, traditional uses, extraction methods, and pharmacological effects of berberine and berberine-containing plants. © 2018 Neag, Mocan, Echeverría, Pop, Bocsan, Crisan and Buzoianu.